A comparative study of Yttrium doped ceria ceramics synthesized using mechanochemical and solid state methods - Ong, Poh Shing; Tan, Yen Ping; Yap, Taufiq Yun Hin; Zainal, Zulkarnain (Universiti Putra Malaysia Press, 2014)
In this work, 10 mol% yttrium-doped ceria powders, Ce0.9Y0.1O1.95, were synthesised using a new mechanical technique, mechanochemical reaction, in which both impact action and shearing forces were applied for efficient fine grinding, subsequently leading to higher homogeneity of the resultant powders. Ce0.9Y0.1O1.95 prepared using this new technique was systematically compared with a sample of the same prepared using conventional solid-state methodology. X-ray diffraction analysis showed all prepared samples were single phase with a cubic fluorite structure. Generally, Y2O3-doped CeO2 electrolytes prepared by mechanochemical reactions were stable at a lower temperature (1100 °C) compared with a sample of the same synthesised using the conventional solid-state method. Characterisations using differential thermal analysis (DTA) and thermogravimetric analysis (TGA) showed no thermal changes and phase transitions, indicating all materials were thermally stable. The electrical properties of the samples investigated by AC impedance spectroscopy in the temperature range 200–800 ˚C are presented and discussed. Scanning electron microscopy (SEM) was used to study the morphology of the materials. Fine-grained powders with uniform grain-size distribution were obtained from the mechanochemical reaction.